Physico-Chemical Analysis of Soil Quality Parameters in Tamilnadu Region An Analytical Approach Towards Life on Land -SDG 15 - R. Vijayaprasath; M Anandaraj; A. Mohamed Ashik (International Journal of Solid State Innovations & Research, 2025)
This study examines the physico-chemical properties of soil in Tamilnadu region, supporting SDG 15’s framework for sustainable land management. Soil, as a vital non-living component, plays a crucial role in ecosystem functioning by facilitating nutrient cycling, retaining water, and supporting habitats for a wide range of organisms. The research analysis key physical parameters (colour, texture, structure, porosity, density, consistency, temperature) and chemical properties, focusing on both macro and micronutrients. Various soil types (loamy, sandy, chalk, peat, silt, clay) are evaluated for their agricultural suitability and ecosystem functions. The analysis emphasizes soil’s role in preventing groundwater contamination and supporting plant stability. This comprehensive assessment aids in understanding soil productivity factors, supporting informed agricultural practices, and contributing to SDG 15’s goals of sustainable terrestrial ecosystem management and soil resource conservation in Tamilnadu’s agricultural landscape.
Keywords: Physico-chemical; Porosity; SDG; density; ecosystem; soil